2010
DOI: 10.1111/j.1472-765x.2010.02874.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with chlorous acid to inhibit spores of Alicyclobacillus acidoterrestris in aqueous suspension and on apples

Abstract: Aim:  To test the efficacy of a chemical (chlorous acid) for reducing the numbers of viable Alicyclobacillus acidoterrestris spores in laboratory media and on apples. Methods and Results:  Alicyclobacillus acidoterrestris spores in aqueous suspension and on apple surfaces of four different cultivars were treated with 268 ppm chlorous acid. Treatment with 268 ppm chlorous acid sharply reduced the numbers of spores of A. acidoterrestris in laboratory media by 1·6, 4·3, and 7·0 log10 reductions for 5, 10, and 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Chlorous acid is a strong oxidizing acid, which has a similar effect and mechanism to chlorine and chlorine dioxide discussed above (Orr and Beuchat ; Lee and others ). Lee and others () found that no matter in laboratory media or on apple surfaces, it was very effective for chlorous acid to reduce an A. acidoterrestris population (Table ). Because Alicyclobacillus spores can survive pasteurization, chemical treatments like chlorous acid hold great promise.…”
Section: Chemical Intervention Treatmentsmentioning
confidence: 99%
“…Chlorous acid is a strong oxidizing acid, which has a similar effect and mechanism to chlorine and chlorine dioxide discussed above (Orr and Beuchat ; Lee and others ). Lee and others () found that no matter in laboratory media or on apple surfaces, it was very effective for chlorous acid to reduce an A. acidoterrestris population (Table ). Because Alicyclobacillus spores can survive pasteurization, chemical treatments like chlorous acid hold great promise.…”
Section: Chemical Intervention Treatmentsmentioning
confidence: 99%
“…The most widely used disinfectant is probably chlorine, but it is only a slow sporicidal and is readily absorbed by organic matter, although there are organic chlorine release agents which are more effective in the presence of soiling (Brown, 2000). Chlorous acid can be used as an alternative sanitizer of chlorine to control a major A. acidoterrestris contamination source in juice processing plants (Lee, Ryu, & Kang, 2010). Lindsay et al (2000) were able to isolate viable spores of Bacillus spp., in particular B. cereus, from alkaline cleaning solutions that had been used for dairy CIP procedures, while Brent Seale et al (2011) demonstrated that exposure to a 1% sodium hydroxide solution enhanced the ability of surviving spores of Geobacillus spp.…”
Section: Cleaning -In -Placementioning
confidence: 99%
“…Intense thermal treatments might also modify fruit juices' quality, nutritional, and sensorial characteristics (Evelyn et al, 2016;. Given these facts, alternative strategies to reduce the contamination in fruit surface immediately before juice extraction have been proposed (Lee et al, 2004(Lee et al, , 2010, such as fruit washing 123 with disinfectants, e.g., peracetic acid (Friedrich et al, 2009;Osopale et al, 2017).…”
Section: Introductionmentioning
confidence: 99%